Effect of influential factors on microbial growth and the correlation between current generation and biomass in an air cathode microbial fuel cell. (7th December 2016) - Li, Na; Kakarla, Ramesh; Min, Booki
Abstract: Microbial biomass in a microbial fuel cell (MFC) was determined at varied external resistances and temperatures, and the current generations were correlated with biomass concentration. MFC operation with wastewater generated the highest current of 0.23 mA at 300 Ω compared with 100 Ω (0.22 mA) and 1000 Ω (0.18 mA). The microbial biomass (0.091 mg-protein/cm 2 ) on the anode with 100 Ω was higher than the other resistances. With growth media, current and biomass density were increased due to high strength electrolyte and nutrient. The MFCs with higher current generation contained a more amount of biomass on an anode electrode. The highest biomass growth rate with growth media was 1.307 × 10 −4  mg-protein/hr·cm 2 at 30 °C (with 300 Ω), which was about 2 times higher than with wastewater. In linear regression, current generation is expected to increase by about 3 times as the biomass is doubled on the anode electrode. Highlights: The amount of biomass on the anode varied depending on operation conditions. Anolyte biomass density was in accordance with the amount of anode biomass. Higher current generation was obtained with anode containing high biomass. Current is expected to increase by 3 times with doubled biomass on anode.